2012
DOI: 10.1123/jsep.34.6.737
|View full text |Cite
|
Sign up to set email alerts
|

Development of, and Initial Validity Evidence for, the Referee Self-Efficacy Scale: A Multistudy Report

Abstract: The purpose of this multistudy report was to develop, and then to provide initial validity evidence for measures derived from, the Referee Self-Efficacy Scale. Data were collected from referees (N = 1609) in the United States (n = 978) and Spain (n = 631). In Study 1 (n = 512), a single-group exploratory structural equation model provided evidence for four factors: game knowledge, decision making, pressure, and communication. In Study 2 (n = 1153), multiple-group confirmatory factor analytic models provided ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 41 publications
7
80
0
6
Order By: Relevance
“…When the relationship between the total score of GSE, and total score of REFS and REFS sub-dimensions is examined, it was found that the highest correlation between was REFS total score and GSE total score and the lowest correlation was between GSE total score and physical competency. Similarly, Myers et al [23] and revealed that all the variables positively and significantly correlated each other when they examined the relationships between the football, basketball and handball referees' physical fitness, game knowledge, decision making, pressure, communication, REFS and GSE total scores. Moreover, examined the relationship between total score of GSE, and total score of REFS and REFS sub-dimensions and found a positive and significant relationship.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…When the relationship between the total score of GSE, and total score of REFS and REFS sub-dimensions is examined, it was found that the highest correlation between was REFS total score and GSE total score and the lowest correlation was between GSE total score and physical competency. Similarly, Myers et al [23] and revealed that all the variables positively and significantly correlated each other when they examined the relationships between the football, basketball and handball referees' physical fitness, game knowledge, decision making, pressure, communication, REFS and GSE total scores. Moreover, examined the relationship between total score of GSE, and total score of REFS and REFS sub-dimensions and found a positive and significant relationship.…”
Section: Discussionmentioning
confidence: 85%
“…However, it was found no significant difference between football, basketball and handball referees' physical fitness sub-dimension and GSE total scores and their ages. Myers et al [23] and concluded that there is a positive and significant difference between game knowledge, decision making, pressure, communication, REFS total scores and refereeing years. Guillén and Feltz [8] stated that refereeing experiences of referees have an impact on their self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations